PROFILE OF THE THESIS TO OBTAIN THE PROFESSIONAL DEGREE IN THE ESCUELA NACIONAL SUPERIOR DE FOLKLORE JOSÉ MARÍA ARGUEDAS - Fuentes Avila, Xavier (2020)
In the present paper, a bibliometric analysis of the theses presented to obtain the professional degree in the Escuela Nacional de Folklore José María Arguedas (La Escuela) which are available in the library of said institution was carried out. 77 theses of a total of 163 were analyzed, in order to quantify the production of research papers at “La Escuela”, conducting a thematic characterization, analyzing the theoretical foundation, reviewing the methodology and conducting a survey on the thematic of the thesis. This study has allowed to observe the tendencies regarding the themes of the theses and the predilection that students show for working with folkloric facts of the coastal and mountain regions of our country. No thesis has been found that focuses on folkloric manifestations of the jungle natural region. It has also been found that the issues related to Regular Basic Education are those that have the most attention, that the themes dedicated to dances visibly exceed those of music and that the number of theses supported has had a remarkable variability which does not allow for the establishment of a trend in the production of theses per year.